Докажите тождество: а) (x-5)²-(x-7)(x-3)=4 б) (x+3)(x-3)-(x-9)(x+1)=8x в) (x-11)(x-1)-(x+6)²=-25 г) (x+1)(x-4)-(x-2)(x+2)=-3x

Докажите тождество: а) (x-5)²-(x-7)(x-3)=4 б) (x+3)(x-3)-(x-9)(x+1)=8x в) (x-11)(x-1)-(x+6)²=-25 г) (x+1)(x-4)-(x-2)(x+2)=-3x
Гость
Ответ(ы) на вопрос:
Гость
а) (x-5)²-(x-7)(x-3)=4 x^2-10x+25-(x^2-3x-7x+21)=4 x^2-10x+25-(x^2-10x+21)=4 x^2-10x+25-x^2+10x-21=4 4=4 б) (x+3)(x-3)-(x-9)(x+1)=8x x^2-9-(x^2+x-9x-9)=8x x^2-9-(x^2-8x-9)=8x x^2-9-x^2+8x+9=8x 8x=8x в)  (x-11)(x-1)-(x+6)²=-25 x^2-x-11x+11-(x^2+12x+36)=-25 x^2-12x+11-(x^2+12x+36)=-25 x^2-12x+11-x^2-12x-36=-25 -24x-25=-25 походу в задании ошибка, чтобы оно получилось должно быть (х-6)^2 г) (x+1)(x-4)-(x-2)(x+2)=-3x x^2-4x+x-4-(x^2-4)=-3x x^2-3x-4-(x^2-4)=-3x x^2-3x-4-x^2+4=-3x -3x=-3x
Не нашли ответ?
Ответить на вопрос
Похожие вопросы